Middle Eastern ceramics unearth in Kampung Baru Archeological Site, Kota Kuala Muda, Kedah, Malaysia - Junko Mori,; Zuliskandar Ramli,; Muhammad Nu’man Mohd Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Kampung Baru Archeological Site is situated in Bujang Valley archaeological area and the site is in Kuala Muda, Kedah to be exact. Past excavations conducted in Bujang Valley have discovered a lot of Middle Eastern ceramics and the archaeological sites which had been found in these excavations were dated from 5th to 12th century AD. Middle Eastern ceramics had been produced in Middle East but have been found not only in Middle East but also in Africa, India, Southeast Asia, China and Japan. Most Middle Eastern ceramics found in Southeast Asia and Far East Asia are Blue-Green Glazed ceramics and the archaeological sites where these ceramics had been found usually dated from 8th to 10th century AD. Many Blue-Green Glazed ceramics are believed to be used as container to transport trade goods and finding of these ceramics can be evidence of trade with Middle Eastern countries. This study employed typological and morphological analysis on the Middle Eastern ceramic that have been discovered at this site. The results of this study found that there were 241 shards of Middle Eastern ceramic discovered in Kampung Baru site and dating for these ceramics is from 8th to 10th century AD.